Green transformational leadership: Systematic literature review (Asian Journal of Economics and Business Management, 2023)
Companies and individuals are cognisant of the gravity of the environmental problem and advocate for the implementation of a sustainable business model. Green behaviour of employees, a form of pro-environmental action at work, is crucial for the organisation to reach its goal of area conservation. To promote Green Transformational Leadership, it is crucial to understand the causes and effects of pro-environmental behaviour, as well as the factors that influence these factors. This systematic literature review offers a comprehensive review of research articles related to green transformational leadership on employee behavior. comes from many articles about the application of green transformational leadership on the performance of presenters and conference participants. systematic review of the literature at issue using the preferred reporting method for systematic reviews and meta-analyses. Analysis of several studies that have links to the benefits of little green transformational leadership on student academic achievement. study points were analyzed using data quality, yielding 30 data points that met the eligibility standard. examination of several journals shows that Green Transformational Leadership has a secret weapon to teach leadership skills to students through the value of harmony, the value of harmony, and students by inviting them to explore their relationships with one another. Empirical results have supported our hypothetical model, showing that green transformational leadership has an indirect influence on green behavior of employees through value alignment, and that this mediating effect can be moderated by green identity.